Sebaceous horn: An interesting case - Saraf Sanjay (Indian Journal of Dermatology, 2007)
Sebaceous horn or cutaneous horn of the nose is a rare clinical entity. A case of a giant sebaceous horn of the nose presenting in an elderly male, which was successfully excised and reconstructed is reported.